Better Management Practices in International Aquaculture - Claude E. Boyd (John Wiley & Sons Ltd., 2025)
The United States imports about 85% of its fi sheries products, and fi sh, shrimp, and molluscan shellfi sh originating from aquaculture are a major component of this trade. Several environmental nongovernmental organizations (NGOs) became highly critical of aquaculture and particularly about marine shrimp and salmon farming in the 1990s. Attempts by more radical environmental NGOs to effect consumer boycotts of these species in the United States and other western nations failed. However, several moderate NGOs persisted in efforts to promote environmental and social responsibility in aquaculture. Criticism of aquaculture practices by World Wildlife Fund, Environmental Defense, Conservation International, and other environmental NGOs has caused aquaculture organizations to promote environmental responsibility, governments to increase environmental regulations for aquaculture, and some retailers and other food service buyers to seek environmentally and socially responsible aquaculture products. Most negative environmental and social impacts of aquaculture occur at the farm level, and particular emphasis has been given to encouraging producers to adopt best management practices (BMPs) designed to lessen these impacts. The NGOs also have succeeded in obtaining the participation of the United Nations Food and Agricultural Organization (FAO), World Bank, and other international development agencies in efforts to promote responsible aquaculture. Moreover, educational programs by NGOs to encourage more responsible seafood choices by consumers apparently are beginning to infl uence the market.